An analysis of the antioxidant activity of Cassia alata and Bauhinia malabarica - Suaco, Thea P.; Mangaliag, Antonio D.; Tapnio, Christopher J. (2015)
The increasing levels of free radicals in the air due to pollution have been implicated to disease, like cancer. Antioxidants typically reduce the level of free radicals by acting as recipients of the extra oxygen preventing the oxidation and damage of cellular components. This study analyzed the potential of Cassia alata and Bauhinia malabarica’s pods and seeds extract as possible antioxidants. Cassia alata and Bauhinia malabarica’s pods and seeds were collected from Ilocos Sur, Philippines. The pods and seeds of the test plants were cut and macerated in 70% ethanol in a 70o C water bath for 10 minutes to obtain the sample extract. Different concentrations were prepared from the pods and seeds of Cassia alata and Bauhinia malabarica. DPPH assay was used in assessing the antioxidant property of the different concentrations of the test plants. The lower the absorbance readings, the more effective it is as an antioxidant. The 200 ug/ml extract of C. alata showed the lowest mean absorbance reading at 0.555 while the 1000 ug/ml of B. malabarica had the lowest mean absorbance reading at 0.774. This means that the said concentrations of C. alata and B. malabarica have the highest antioxidant activity as shown by its free radical scavenging ability.
Keywords: Antioxidants -- Health aspects